2017 White Paper on recent issues in bioanalysis: aren't BMV guidance/guidelines 'Scientific'? (Part 1 – LCMS: small molecules, peptides and small molecule biomarkers). (December 2017) - Welink, Jan; Yang, Eric; Hughes, Nicola; Rago, Brian; Woolf, Eric; Sydor, Jens; Coppola, Laura; Ackermann, Brad; Li, Wenkui; Alley, Stephen C; Arnold, Mark; Berger, Isabella; et al.
The 2017 11th Workshop on Recent Issues in Bioanalysis (11th WRIB) took place in Los Angeles/Universal City, California from 3 April 2017 to 7 April 2017 with participation of close to 750 professionals from pharmaceutical/biopharmaceutical companies, biotechnology companies, contract research organizations and regulatory agencies worldwide. WRIB was once again a 5-day, weeklong event – A Full Immersion Week of Bioanalysis, Biomarkers and Immunogenicity. As usual, it was specifically designed to facilitate sharing, reviewing, discussing and agreeing on approaches to address the most current issues of interest including both small and large molecule analysis involving LCMS, hybrid LBA/LCMS and ligand-binding assay (LBA) approaches. This 2017 White Paper encompasses recommendations emerging from the extensive discussions held during the workshop, and is aimed to provide the bioanalytical community with key information and practical solutions on topics and issues addressed, in an effort to enable advances in scientific excellence, improved quality and better regulatory compliance. Due to its length, the 2017 edition of this comprehensive White Paper has been divided into three parts for editorial reasons. This publication (Part 1) covers the recommendations for Small Molecules, Peptides and Small Molecule Biomarkers using LCMS. Part 2 (Biotherapeutics, Biomarkers and Immunogenicity Assays using Hybrid LBA/LCMS and Regulatory Agencies' Inputs) and Part 3 (LBA: Immunogenicity, Biomarkers and PK Assays) are published in volume 9 of Bioanalysis, issues 23 and 24 (2017), respectively.